2007
DOI: 10.1038/ismej.2007.1
|View full text |Cite
|
Sign up to set email alerts
|

Recovery in culture of viable but nonculturable Vibrio parahaemolyticus: regrowth or resuscitation?

Abstract: The objective of this study was to explore the recovery of culturability of viable but nonculturable (VBNC) Vibrio parahaemolyticus after temperature upshift and to determine whether regrowth or resuscitation occurred. A clinical strain of V. parahaemolyticus Vp5 was rendered VBNC by exposure to artificial seawater (ASW) at 41C. Aliquots of the ASW suspension of cells (0.1, 1 and 10 ml) were subjected to increased temperatures of 201C and 371C. Culturability of the cells in the aliquots was monitored for colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 35 publications
(27 reference statements)
2
43
0
1
Order By: Relevance
“…populations in artificial and natural seawater has been extensively studied, and it has been demonstrated that nutrient deprivation, elevated salinity, and/ or reduced temperature strongly induce transition to the VBNC state [5,[38][39][40]. Analysis of Vibrio responses to the environmental factors revealed some common features OM outer membrane, P periplasm, CM cytoplasmic membrane, C cytoplasmic, NCyt noncytoplasmic according to PSORTb 3.0 program including the stress-induced changes in cell physiology and morphology [15,41].…”
Section: Discussionmentioning
confidence: 99%
“…populations in artificial and natural seawater has been extensively studied, and it has been demonstrated that nutrient deprivation, elevated salinity, and/ or reduced temperature strongly induce transition to the VBNC state [5,[38][39][40]. Analysis of Vibrio responses to the environmental factors revealed some common features OM outer membrane, P periplasm, CM cytoplasmic membrane, C cytoplasmic, NCyt noncytoplasmic according to PSORTb 3.0 program including the stress-induced changes in cell physiology and morphology [15,41].…”
Section: Discussionmentioning
confidence: 99%
“…In coastal water, during winter months, when SST dips below the preferred range, most vibrios can enter a dormant state known as "viable but nonculturable" (VBNC) (54,55). Other factors, both chemical and environmental, which have been reported to induce the VBNC state, are diverse and numerous.…”
Section: Effect Of Increasing Sst On Vibrio Growth and Biology: Fieldmentioning
confidence: 99%
“…It is therefore crucial to eliminate any active cells from the dormant culture before carrying out the resuscitation procedure as the presence of only a few culturable cells in a VBNC cell suspension of interest could give false resuscitation results. 5 In the past, many techniques have been employed to prepare, isolate, and study bacterial cells that are viable but unable to multiply. [1][2][3]6,7 Unfortunately, many of these techniques are time consuming and labor intensive, and it is therefore necessary to look for rapid techniques for the separation of dormant from nondormant cells.…”
Section: Introductionmentioning
confidence: 99%